The path to gay rights : how activism and coming out changed public opinion - Garretson, Jeremiah J. (New York University Press, 2018)
An innovative, data-driven explanation of how public opinion shifted on LGBTQ rights The Path to Gay Rights is the first social science analysis of how and why the LGBTQ movement achieved its most unexpected victory--transforming gay people from a despised group of social deviants into a minority worthy of rights and protections in the eyes of most Americans. The book weaves together a narrative of LGBTQ history with new findings from the field of political psychology to provide an understanding of how social movements affect mass attitudes in the United States and globally. Using data going back to the 1970s, the book argues that the current understanding of how social movements change mass opinion--through sympathetic media coverage and endorsements from political leaders--cannot provide an adequate explanation for the phenomenal success of the LGBTQ movement at changing the public's views. In The Path to Gay Rights, Jeremiah Garretson argues that the LGBTQ community's response to the AIDS crisis was a turning point for public support of gay rights. ACT-UP and related AIDS organizations strategically targeted political and media leaders, normalizing news coverage of LGBTQ issues and AIDS and signaled to LGBTQ people across the United States that their lives were valued. The net result was an increase in the number of LGBTQ people who came out and lived their lives openly, and with increased contact with gay people, public attitudes began to warm and change. Garretson goes beyond the story of LGBTQ rights to develop an evidence-based argument for how social movements can alter mass opinion on any contentious topic.